Analisis kebutuhan diklat jabatan wakil kepala sekolah kurikulum sekolah dasar - Nacep Hamrat; Rusman Rusman (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2021)
This study aims to analyze the training needs of vice-principals in the curriculum field. Respondents in this study were vice-principals of the curriculum affair in Central Jakarta. The number of respondents in this study were 58 vice-principals from Cempaka Putih, Johar Baru, Senen, and Kemayoran. This study used a quantitative research method with survey techniques. The data collection instrument used was a vice principal competency questionnaire consisting of five competencies: personal and social competencies, leadership competencies, school development competencies, entrepreneurial competencies, and task field competencies (curriculum development). The data analysis carried out was univariate data analysis by looking at each competency's indicator achievements. The results showed that respondents with undergraduate qualifications had gaps in leadership competencies, school development, entrepreneurship, and curriculum development. Respondents with master qualifications have gaps in curriculum development competencies. The research results can be used as recommendations for developing a training program to strengthen the competence of vice-principals of the curriculum affair in Central Jakarta.